SULAM PITA AIA TABIK AMPANG GADANG AMPEK ANGKEK (Kajian Motif Hias, Teknik, dan Bentuk Produk) - Dra. Minarsih, M.Sn., PERMATA SARI, Drs. Erwin A, M.Sn., (Serupa The Journal of Art Education, 2017)
This research is constituted by, lack of information and knowledge society, especially in Ampek Angkekon the shape of ornamental motifs, techniques, and product shape ribbon on a patchwork effort F + M Creative. The purpose of this study was to: Describe 1) decorative motif 2) techniques 3) the product shape ribbon on a patchwork effort F + M Creative. The theory used is the theory of culture, embroidery, ribbon embroidery, motifs, techniques and forms. This study used a qualitative method with descriptive approach. Research Location in Aia Tabik, Ampang Gadang, Ampek Angkek, Agam. Subjects were informants who know about the ribbon. Source data contains data written records, image recording, and literature study.The results showed that the decorative motif ribbon embroidery on embroidery business F + M Creative sourced from flora and geometric shapes. The names of the motive, namely: marigolds flower ornamental motifs, decorative motif chrysanthemums, roses and ornamental motifs. Ribbon embroidery technique using the techniques: chain stitc, leaf stitch, spider web rose, french knots, puncture flying stitch, chain knots, baste skewers, and a chain stitch. Forms of manufactured products: the veil, mukenah, clothes, handbags, brooches hijab, cornertable mats, towels, seat cushions and tablecloth. Conclusion decorative motifs embroidered effort F + M Creative sourced from flora and geometric. Technique: chain stitch, leaf stitch, spider web rose, french knots, puncture flying stitch, chain knots, baste skewers, and a chain stitch. Product form: the veil, clothes, handbags, brooches hijab, corner table mats, towels, seat cushions and tablecloths.Keyword: Ribbon Embroidery